Dietary Regimen and Physical Activity in University Students - Champutiz-Ortiz, Eliana (2024)
ABSTRACT Introduction: The adolescent who enters university goes on to a highly demanding educational system on an intellectual, emotional and even physical level in many cases. In this complicated stage, he faces new and progressive academic demands, outside his family and social environment, this causes stress and changes in his diet and physical activity; This leads to inadequate nutrition and increased risk factors for the development of metabolic, cardiovascular and endocrine diseases. Objective: To determine the variations in the diet and physical activity in Clinical Laboratory students of the Central University of Ecuador, 2021-2022. Material and Methods: This cross-sectional analytical study assessed changes in dietary habits and physical activity among 46 students of both sexes, 18 to 22 years old, at the beginning and end of their first university year. Results: The findings indicate significant changes in dietary and physical behavior of university students (p-value <0,05). A decrease in physical activity and consumption of fruits and vegetables will be observed, along with an increase in sedentary behavior and a preference for non-home-cooked food. These changes could adversely affect student’s health as they adapt to university life. Conclusions: The study highlights negative variations in the habits of students in their first year of university, emphasizing the need to implement intervention strategies, promoting of healthy practices to reduce the risk of chronic degenerative diseases in this demographic group.